1996
DOI: 10.1046/j.1471-4159.1996.66020817.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation and Activation of Tryptophan Hydroxylase by Exogenous Protein Kinase A

Abstract: The catalytic subunit of protein kinase A increases brain tryptophan hydroxylase activity. The activation is manifested as an increase in Vrnax without alterations in the Km for either tetrahydrobiopterin or tryptophan. The activation of tryptophan hydroxylase by protein kinase A is dependent on ATP and an intact kinase and is inhibited specifically by protein kinase A inhibitors. Protein kinase A also catalyzes the phosphorylation of tryptophan hydroxylase. The extent to which tryptophan hydroxylase is phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
6

Year Published

1998
1998
2007
2007

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 15 publications
0
29
0
6
Order By: Relevance
“…It may be phosphorylated by the cAMP-dependent protein kinase (PKA) (Ehret et al, 1991;Johansen et al, 1995Johansen et al, , 1996, a Ca 2ϩ /calmodulin (CaM)-dependent protein kinase (PKCa 2ϩ /CaM) (Ehret et al, 1989) and PKC (Ehret, 1994). In the pineal gland, it has been demonstrated that stimulation of PKA induces TPOH activation.…”
Section: B Tryptophan Hydroxylasementioning
confidence: 99%
See 1 more Smart Citation
“…It may be phosphorylated by the cAMP-dependent protein kinase (PKA) (Ehret et al, 1991;Johansen et al, 1995Johansen et al, , 1996, a Ca 2ϩ /calmodulin (CaM)-dependent protein kinase (PKCa 2ϩ /CaM) (Ehret et al, 1989) and PKC (Ehret, 1994). In the pineal gland, it has been demonstrated that stimulation of PKA induces TPOH activation.…”
Section: B Tryptophan Hydroxylasementioning
confidence: 99%
“…1) Activation of the cAMP/PKA pathway is the major nocturnal event that stimulates MEL synthesis Klein et al, , 1996Berg and Klein, 1971;Roseboom et al, 1996). Although the daytime levels of Tpoh mRNA and activity are elevated, activation of the cAMP/PKA pathway induces a small (13%) nocturnal increase in Tpoh gene expression, probably through the effect of P-CREB (Besançon et al, 1996 and phosphorylation/activation of TPOH (Johansen et al, 1995(Johansen et al, , 1996. These events result in a 2-fold nocturnal increase in TPOH activity (Ehret et al, 1991).…”
Section: The Third Messengers/transcription Factorsmentioning
confidence: 99%
“…The enzyme is present in four structures: the pineal gland, the serotonergic neurons in the raphe nuclei that project in all brain areas, the enterochromaffin cells, and the myenteric neurons in the gut (21,22). TPH activity is modulated posttranscriptionally by phosphorylation (23)(24)(25), and protein isoforms from the brainstem and pineal gland, differing in physicochemical properties, have been identified possibly because of posttranscriptional events (26). The TPH cDNA was first isolated from rat pineal gland (27,28) and used to study the regulated expression of the tph gene (29,30).…”
mentioning
confidence: 99%
“…A fosforilação da TPH pode ser feita pela PKA, pela quinase dependente de cálcio e calmodulina (CaMK) e pela PKC (EHRET et al, 1989;MAITRE, 1991;JOHANSEN et al, 1995JOHANSEN et al, , 1996RIBELAYGA, 2003).…”
Section: Triptofano Hidroxilaseunclassified